The Relationship Between Physical Activity and Dietary Patterns with Menstrual Cycles Among Female Medical Students of YARSI University Class of 2023 and Its Review from an Islamic Perspective - Handayani, Putri; Purbo Astuti, Ike Irmawati; Anshar, Muhammad Fazlurrahman; Syam, Edward (Fakultas Kedokteran Universitas YARSI, 2025)
Menstruation is a biological process influenced by various factors, including lifestyle choices such as physical activity and dietary patterns. This study aims to analyze the relationship between physical activity and dietary patterns with menstrual cycles among female medicaly students at YARSI University Class of 2023 and to review these findings from an Islamic perspective. This cross-sectional study involved 73 female students selected through purposive sampling. Data were collected using an online questionnaire covering dietary habits, physical activity, and menstrual cycles. The results revealed that the majority of respondents engaged in moderate-intensity physical activity (75.4%) and had unhealthy dietary patterns (64.4%). Most participants (65.8%) had normal menstrual cycles, while 28.8% experienced polymenorrhea and 5.5% experienced oligomenorrhea. Bivariate analysis using the Chi-Square test showed no significant relationship between physical activity (p = 0.674) and dietary patterns (p = 0.18) with menstrual cycles. In the Islamic perspective, maintaining health involves adopting a healthy lifestyle by consuming halal and thayyib food, moderate physical activity, and a balance of physical and spiritual. The study concludes that there is no significant relationship between physical activity and dietary patterns with menstrual cycles among the respondents. The Islamic perspective emphasizes the importance of a healthy lifestyle as a means to support worship and physical well-being.